Sistem kerja Four-handed dentistry dalam praktek dokter gigi (Fourhanded dentistry system in dental practice) - Sukmasari, Susi (Faculty of Dentistry - Padjadjaran University, 2006)
Researchs have been shown that suffering diseases in dental health team are RSI and WMSDs, which caused by activities in dental clinic. Sophisticated equipments will not solve the problem if they are not supported by the cooperation technique from dental health team. To prevent these problems is to apply an effective and efficient technique, so it can prevent various disease above. Four-handed dentistry technique which have been known since 1960, now become trend return, because dentist's goal in this decade is to improve productivity and eliminate stress during working in dental clinic. Four-handed-dentistry is a part of ergonomic dental application, in the form of ergonomic procedure, which is an eficcient and effective procedure in the clinic for operator and assistant.